2011
DOI: 10.5090/kjtcs.2011.44.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Valve Replacement for Aortic Stenosis and Concomitant Coronary Artery Bypass: Long-term Outcomes and Predictors of Mortality

Abstract: BackgroundWe evaluated the surgical results and predictors of long-term survival in patients who underwent coronary artery bypass grafting (CABG) at the time of an aortic valve replacement (AVR) due to aortic stenosis.Materials and MethodsBetween January 1990 and December 2009, 183 consecutive patients underwent CABG and concomitant aortic valve replacement for aortic stenosis. The mean follow-up period was 59.8±3.3 months and follow-up was possible in 98.3% of cases. Predictors of mortality were determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In Formica et al [21] the study revealed that the iAVR group exhibited higher EF% (56.7% vs. 54%, respectively; p = 0.028) and higher aortic peak gradients relative to combined procedures, but showed no differences in m. AVA between the two groups. Furthermore, previous studies indicated that a low EF increased the risk of undergoing AVR-CABG [1,8,22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Formica et al [21] the study revealed that the iAVR group exhibited higher EF% (56.7% vs. 54%, respectively; p = 0.028) and higher aortic peak gradients relative to combined procedures, but showed no differences in m. AVA between the two groups. Furthermore, previous studies indicated that a low EF increased the risk of undergoing AVR-CABG [1,8,22] .…”
Section: Discussionmentioning
confidence: 99%
“…Aortic stenosis and coronary atherosclerosis may cause myocardial ischemia and its consequences, including angina, myocardial infarction, and mortality independently [1] .…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the mortality rates of hospitals that have a low number of heart surgeries, consideration is needed for the diverse situations of each hospitals and analysis regarding the particular high mortality rates. For heart surgeries, the clinical conditions of the patients, such as comorbidity and emergency surgeries, have a significant impact in the treatment outcomes [12,13]. …”
Section: Discussionmentioning
confidence: 99%